Premolar root and canal variation in South African Plio-Pleistocene specimens attributed to Australopithecus africanus and Paranthropus robustus. Issue 93 (April 2016) - Moore, N. Collin; Thackeray, J. Francis; Hublin, Jean-Jacques; Skinner, Matthew M.
Abstract: South African hominin fossils attributed to Australopithecus africanus derive from the cave sites of Makapansgat, Sterkfontein, and Taung, from deposits dated between about 2 and 3 million years ago (Ma), while Paranthropus robustus is known from Drimolen, Kromdraai, and Swartkrans, from deposits dated between about 1 and 2 Ma. Although variation in the premolar root complex has informed taxonomic and phylogenetic hypotheses for these fossil hominin species, traditionally there has been a focus on external root form, number, and position. In this study, we use microtomography to undertake the first comprehensive study of maxillary and mandibular premolar root and canal variation in Australopithecus africanus and Paranthropus robustus ( n = 166 teeth) within and between the species. We also test for correlations between premolar size and root morphology as predicted under the 'size/number continuum' (SNC) model, which correlates increasing root number with tooth size. Our results demonstrate previously undocumented variation in these two fossil hominin species and highlight taxonomic differences in the presence and frequency of particular root types, qualitative root traits, and tooth size (measured as cervix cross-sectional area). Patterns of tooth size and canal/root number are broadly consistent with the SNC model, however statistically significant support is limited. The implications for hominin taxonomy in light of the increased variation in root morphology documented in this study are discussed.